2021
DOI: 10.3389/fimmu.2021.661052
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Induces Lymphocytopenia by Promoting Inflammation and Decimates Secondary Lymphoid Organs

Abstract: While lymphocytopenia is a common characteristic of coronavirus disease 2019 (COVID-19), the mechanisms responsible for this lymphocyte depletion are unclear. Here, we retrospectively reviewed the clinical and immunological data from 18 fatal COVID-19 cases, results showed that these patients had severe lymphocytopenia, together with high serum levels of inflammatory cytokines (IL-6, IL-8 and IL-10), and elevation of many other mediators in routine laboratory tests, including C-reactive protein, lactate dehydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
79
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(86 citation statements)
references
References 39 publications
6
79
1
Order By: Relevance
“…SARS-CoV-2 infection in CD169 + macrophages has been reported in COVID-19 15,52 . To validate our findings of SARS-CoV-2 infection in CD169 + macrophages, lung tissues from rhesus macaques following SARS CoV-2 infection and healthy controls were stained for CD68, ACE2, SIGLEC1, MX1, MX2, ISG15, Complement component 1q (C1q) and SARS CoV-2 nucleocapsid antibody (Fig5 b-h, j, S5-12).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…SARS-CoV-2 infection in CD169 + macrophages has been reported in COVID-19 15,52 . To validate our findings of SARS-CoV-2 infection in CD169 + macrophages, lung tissues from rhesus macaques following SARS CoV-2 infection and healthy controls were stained for CD68, ACE2, SIGLEC1, MX1, MX2, ISG15, Complement component 1q (C1q) and SARS CoV-2 nucleocapsid antibody (Fig5 b-h, j, S5-12).…”
Section: Resultsmentioning
confidence: 99%
“…ScRNAseq has recently identified initial cellular targets of SARS-CoV-2 infection in model organisms 6-8 and patients 9-13 and characterized peripheral and local immune responses in severe COVID-19 14 , with severe disease being associated with a cytokine storm and increased neutrophil accumulation. However, the human studies have mostly been performed in peripheral blood samples 14 , BAL 9 and tissues 8,15 from a limited number of moderate or severe COVID-19 patients within limited age ranges. To overcome the limitations associated with longitudinal early immune profiling in human subjects and to get more in-depth understanding of the early dynamics of transcriptional changes during COVID-19, we characterized the transcriptional signatures at the single cell level in the broncho-alveolar compartment of rhesus macaques at pre-infection collected 7 days before infection (−7dpi), at early stage of SARS-CoV-2 infection (3dpi) and at endpoint of the study (14-17dpi).…”
Section: Introductionmentioning
confidence: 99%
“…Besides the expected detection of positive and negative strand transcripts in epithelial cells, viral reads were also detected in subsets of macrophages suggesting that AMs harbor SARS-CoV-2 and allow viral replication in vivo (158), challenging the results on abortive infection gained from in vitro experiments. Interestingly, immunostaining of post-mortem tissue from patients who had died from COVID-19 revealed the presence of SARS-CoV-2 nucleoprotein in and the expression of ACE2 on populations of CD169 + macrophages in lymph nodes and the spleen (20). Given the increasing body of evidence in support of active infection of and the indication of productive viral replication in AMs by SARS-CoV-2, Grant et al have come up with the hypothesis that AMs may act as a Trojan horse, transferring the virus to adjacent lung regions, thereby slowly propagating SARS-CoV-2 infection and spreading hyperinflammation across the lung (Figure 1).…”
Section: Detection Of Sars-cov-2 Rna In Single-cell Rna Profiles Of Monocytes and Macrophagesmentioning
confidence: 99%
“…Both lymphocyte subsets showed a distinct reduction in numbers on admission to ICU, which is in line with studies pointing to functional exhaustion and an impaired cytotoxic response in COVID-19 patients [ 54 ]. Excessive production of IL-6 might suppress lymphopoiesis [ 55 ] and SARS-CoV-2 can induce cell death via Fas/FasL-dependent signaling [ 56 ]. We have previously shown that inflammation and viral loads were drastically reduced after two weeks of intensive care in patients with COVID-19 induced ARDS and antibody titers against the spike receptor binding domain of the virus were fully established at this point of time [ 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%